Galectin-3 Impairment of MYCN-Dependent Apoptosis-Sensitive Phenotype Is Antagonized by Nutlin-3 in Neuroblastoma Cells - Veschi, Veronica; Petroni, Marialaura; Cardinali, Beatrice; Dominici, Carlo; Screpanti, Isabella; Frati, Luigi; Bartolazzi, Armando; Gulino, Alberto; Giannini, Giuseppe (PLOS ONE, 2012)
MYCN amplification occurs in about 20–25% of human neuroblastomas and characterizes the majority of the high-risk cases, which display less than 50% prolonged survival rate despite intense multimodal treatment. Somehow paradoxically, MYCN also sensitizes neuroblastoma cells to apoptosis, understanding the molecular mechanisms of which might be relevant for the therapy of MYCN amplified neuroblastoma. We recently reported that the apoptosis-sensitive phenotype induced by MYCN is linked to stabilization of p53 and its proapoptotic kinase HIPK2. In MYCN primed neuroblastoma cells, further activation of both HIPK2 and p53 by Nutlin-3 leads to massive apoptosis in vitro and to tumor shrinkage and impairment of metastasis in xenograft models. Here we report that Galectin-3 impairs MYCN-primed and HIPK2-p53-dependent apoptosis in neuroblastoma cells. Galectin-3 is broadly expressed in human neuroblastoma cell lines and tumors and is repressed by MYCN to induce the apoptosis-sensitive phenotype. Despite its reduced levels, Galectin-3 can still exert residual antiapoptotic effects in MYCN amplified neuroblastoma cells, possibly due to its specific subcellular localization. Importantly, Nutlin-3 represses Galectin-3 expression, and this is required for its potent cell killing effect on MYCN amplified cell lines. Our data further characterize the apoptosis-sensitive phenotype induced by MYCN, expand our understanding of the activity of MDM2-p53 antagonists and highlight Galectin-3 as a potential biomarker for the tailored p53 reactivation therapy in patients with high-risk neuroblastomas.